2021
DOI: 10.1038/s41467-021-22399-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis to identify genes associated with selective hippocampal vulnerability in Alzheimer’s disease

Abstract: Selective vulnerability of different brain regions is seen in many neurodegenerative disorders. The hippocampus and cortex are selectively vulnerable in Alzheimer’s disease (AD), however the degree of involvement of the different brain regions differs among patients. We classified corticolimbic patterns of neurofibrillary tangles in postmortem tissue to capture extreme and representative phenotypes. We combined bulk RNA sequencing with digital pathology to examine hippocampal vulnerability in AD. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 99 publications
(95 reference statements)
3
44
0
Order By: Relevance
“…However, when we removed three AD cases with RIN < 5 from our analyses and matched groups by RIN, three out of five genes investigated still displayed significant correlations when normalized to RPL30 . This result corroborates a recent RNA-seq study which found that RIN affected differential gene expression analysis of AD HP tissue compared to normal HP tissue even with a RIN cut-off of 7 ( Crist et al, 2021 ). Thus, this study and others have recommended that RIN is included as a co-variate during statistical analyses ( Crist et al, 2021 ; Guennewig et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, when we removed three AD cases with RIN < 5 from our analyses and matched groups by RIN, three out of five genes investigated still displayed significant correlations when normalized to RPL30 . This result corroborates a recent RNA-seq study which found that RIN affected differential gene expression analysis of AD HP tissue compared to normal HP tissue even with a RIN cut-off of 7 ( Crist et al, 2021 ). Thus, this study and others have recommended that RIN is included as a co-variate during statistical analyses ( Crist et al, 2021 ; Guennewig et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…This result corroborates a recent RNA-seq study which found that RIN affected differential gene expression analysis of AD HP tissue compared to normal HP tissue even with a RIN cut-off of 7 ( Crist et al, 2021 ). Thus, this study and others have recommended that RIN is included as a co-variate during statistical analyses ( Crist et al, 2021 ; Guennewig et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Transcriptome analysis of the postmortem human brain tissue 28 32 or genetically modified animal models 33 38 has provided a comprehensive overview of the transcriptional responses associated with AD pathogenesis. In particular, AICD has been proposed as a key epigenetic regulator of gene expression controlling a diverse range of genes.…”
Section: Discussionmentioning
confidence: 99%
“…The atrophy of the hippocampus, essential for memory formation and consolidation [ 9 , 13 , 49 ], is associated with memory impairment in normal ageing [ 34 ] and is predictive of Alzheimer’s disease (AD) and associated dementia [ 3 , 26 ]. The hippocampus is one of the most severely affected brain regions in AD and dementia with Lewy Bodies (DLB) [ 4 , 20 , 28 , 64 ] but the causes of its vulnerability are still poorly understood. The hippocampal architecture has been widely studied for its tri-synaptic loop circuitry and its composition in five distinct subfields, the dentate gyrus (DG), as well as the four Cornu ammonis (CA) fields [ 8 ] dedicated to specific types or sequences of memory processes [ 18 , 82 , 94 ].…”
Section: Introductionmentioning
confidence: 99%